ADUBAÇÃO NITROGENADA E INOCULAÇÃO DE Azospirillum brasilense PARA A PRODUÇÃO DE MILHO E TRIGO EM SISTEMA PLANTIO DIRETO - Bini, Angelo Rafael (2015)
The adequate supply of nitrogen (N) is essential for obtaining high grain yields. However, use of high doses of N can reduce the efficiency of using the N and cause environmental contamination. The supply of N through biological fixation on corn and wheat may contribute to the sustainability of agricultural production. This study was carried out with the purpose of evaluate (i) the soil chemical attributes after seed inoculation with Azospirillum brasilense and the application of nitrogen in top dressing and (ii) plant nutrition, grain yield, nutrient uptake and N use efficiency in corn and wheat on the basis of seed inoculation with Azospirillum brasilense and nitrogen fertilization. The experiment was conducted in Ponta Grossa (PR) on a very loamy, kaolinitic, thermic Typic Hapludox (Oxisol) for 34 years under no-tillage. The experimental design used was a randomized block, in a split plot arrangement, with three replications. The plots were employed treatments with and without seed inoculation with Azospirillum brasilense and the subplots were applied four doses of nitrogen in the form of urea in corn (0, 80, 160 and 240 kg ha-1) and wheat (0, 40, 80 and 120 kg ha-1). Corn was cultivated after black oat and wheat was grown after corn. Soil samples collected at 0-10, 10-20 and 20-40 cm depths, after corn harvest, revealed no changes in pH and Al, Ca, Mg, K, P and S-SO42 - depending on the inoculation with Azospirillum, and it was observed increase in Mg content in the 10-20 cm layer in response to nitrogen fertilization. Seeds inoculation with Azospirillum did not affect the leaf contents of macronutrients in maize and wheat, and doses of nitrogen in increased levels of N, P and S in corn leaves, and N, K and Ca in the leaves wheat. The corn production was hampered by inoculation with Azospirillum without N fertilization and was favored by Azospirillum when the highest dose of N was applied (240 kg ha-1). In wheat crop, inoculation with Azospirillum increased grain yield in the treatments without N and 40 and 80 kg N ha-1, and depressed grain yield when the highest dose of N (120 kg ha-1) was applied cover. The nitrogen fertilization increased the productivity of maize and wheat grain, both in the absence and in the presence of inoculation with Azospirillum. Seeds inoculation with Azospirillum did not alter the nutrient uptake by corn and increased the extraction of P and S for the wheat crop. Nitrogen fertilization resulted in increased coverage in the extraction of N, P, Ca, Mg and S for corn, and K11 and S for wheat. Inoculation with Azospirillum favored the extraction of N for wheat crop only in the plots without N and application of the lower dose of N (40 kg ha-1) in coverage. The nitrogen fertilization increased the extraction of N for wheat crop with or without Azospirillum. Seeds inoculation with Azospirillum increased agronomic efficiency (EA) of nitrogen fertilization in corn and caused increase in the Partial Factor Productivity of N (FPPN) in wheat crop when the lowest dose of N (40 kg ha-1) was applied to cover. Inoculation of maize and wheat seeds with Azospirillum brasilense, associated with the adjustment of nitrogen fertilization, proved to be feasible capable to maximize grain yield crops in no-tillage system.